2011
DOI: 10.1159/000322689
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Cancer Surveillance in a High-Risk Population in Tuscany (Central Italy): Preliminary Results

Abstract: Background/Aims: The surveillance of subjects at high risk for developing gastric cancer (GC) may represent an effective strategy for reducing specific morbidity and mortality. The aim of this study was to identify GC at its initial phase and to identify precancerous lesions in a group of GC high-risk subjects. Methods: We enrolled first-degree relatives of patients affected by GC who resided in a GC high-risk area (Tuscany, Central Italy). The study’s protocol included the collection of several individual mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…In order to develop sensitive and specific therapies against GC, molecular biomarkers must be determined (24). Abnormal expression levels of members of the Sox gene family usually correlate with malignant and metastatic tumors (16,25).…”
Section: Discussionmentioning
confidence: 99%
“…In order to develop sensitive and specific therapies against GC, molecular biomarkers must be determined (24). Abnormal expression levels of members of the Sox gene family usually correlate with malignant and metastatic tumors (16,25).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the reported studies are cross-sectional studies in which the serologic test was performed simultaneously with upper endoscopic screening. Although several studies have been reported from European countries, their outcomes were mainly for chronic atrophic gastritis which is a surrogate endpoint even if it can be a precursor of gastric cancer [33][34][35] . Lomba-Viana et al [36] previously reported the results of a 5-year follow-up study of the serum pepsinogen test for the early detection of gastric cancer in Portugal.…”
Section: Endoscopic Screeningmentioning
confidence: 99%
“…This study as a free standing cost analysis, despite its inability to compute the cost-effectiveness ratio, provided important empirical evidence for programme management and ultimately for value-for-money decision making. Cost studies of long-term GC surveillance have long been anticipated worldwide given that research already illustrated the benefit of GC surveillance [27,28]. Exploring the mechanisms underlying our results would be of universal interest to GC researchers.…”
Section: Discussionmentioning
confidence: 91%